Reconciling ambivalent gendered experiences platform logics and Filipino trans women on Facebook - Co, Reena Bianca M.; Oboy, John Carlo C.
Although ambivalence research has been the subject of much scholarly investigation, it is limited to its earthly symptoms, with few studying its presence in media. Some of these studies include the paradox of trans women's lived realities online, but sadly, they do not interrogate the discursive work of platforms in the constructions of ambivalence, including how users harness parts of them for their reconciliation. Borrowing from Risman's (2017) gender structure theory, Baxter and Montgomery's (1996) relational dialectics theory, and Abeele et al.'s (2018) anytime, anyplace connectivity, we address these gaps in three stages: First, by identifying Filipino trans women's ambivalent gendered experiences on Facebook, second by reverse-engineering the platform's logic, and third, describing the users' communicative and sociotechnical reconciliation strategies. Data was generated from 20 interviews, 15 profile observations, and 15 textual analyses. Findings show that contradictions emerge from interactions within Facebook's software assemblage informed by its social, network, personal, public, and legibility logic. In response, informants negotiate against these structures through agentic and deterministic reconciliation. We observed that dialectical relationships fluctuate in command, offering insights into how users remap platforms through their gendered practice and vice versa.